(untitled) (Research, Society and Development, 2020)
The pequi is a native specie from the Brazilian Cerrado that has great economic importance for the population of the region. The pericarp is considered an agroindustrial residue despite corresponding to approximately 80% of the total fruit mass. Informations about the chemical composition of pericarp would allow better utilization of this portion of the fruit. The objective of this study was to identify the best conditions of agitation, extraction time and extraction temperature to maximize the extraction of volatile organic compounds present in pequi pericarp (Caryocar brasiliense Camb.) using two types of solid phase microextraction fibers. The extraction of the volatile compounds was using the headspace solid-phase microextraction method with subsequent separation and identification by CG-MS. Polydimethylsiloxane/divinylbenzene (PDMS/DVB) fiber was statistically more efficient than divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) fiber. The both fibers enabled the extraction and identification of 35 compounds, mainly terpenes (65.71%) and esters (14.29%). An increase in the extraction temperature and time allowed greater extraction of volatile compounds by both fibers. However, in relation to agitation, the best condition for using DVB/CAR/PDMS was 100 rpm, while agitation was not necessary for an efficient extraction using the PDMS/DVB fiber.